Investigation of Vasculogenesis Inducing Biphasic Scaffolds for Bone Tissue Engineering - Pekozer, Gorke Gurel; Akar, Nergis Abay; Cumbul, Alev; Beyzadeoglu, Tahsin; Kose, Gamze Torun (AMER CHEMICAL SOC, 2021)
Vascularization is the main obstacle for the bone tissue engineering strategies since the defect size is generally large. Incorporation of angiogenic factors is one of the strategies employed in order to accelerate vascularization and improve bone healing. In this study, a biphasic scaffold consisting of fibrous poly(lactide-co-glycolide) (PLGA) and poly(lactide-co-glycolide)block- poly( ethylene glycol)-block-poly(lactide-co-glycolide) (PLGA-PEG-PLGA) hydrogel loaded with vascular endothelial growth factor-A (VEGF) inducer, GS4012, was constructed. Mesenchymal stem cells isolated from rat bone marrow (rBMSCs) were used for differentiation into osteogenic cells, and endothelial cells isolated from rat peripheral blood (rPBECs) were used to test the in vitro endothelial cell recruitment. The biphasic scaffold was tested for cell proliferation, ALP expression, VEGF induction, expression of osteogenic genes by rBMSCs, and recruitment of rPBECs in vitro and for improved bone healing and vascularization in vivo on critical size rat cranial defects. Endothelial migration through porous insert and VEGF induction were obtained in vitro in response to GS4012 as well as the upregulation of ALP, Runx2, Col I, and OC gene expressions. The biphasic scaffold was also shown to be effective in improving endothelial cell recruitment, vascularization, and bone healing in vivo. Thus, the proposed design has a great potential for the healing of critical size bone defect in tissue engineering studies according to both in vitro and in vivo investigations.
Keywords: GS4012; vascularization; bone tissue engineering; wet spinning; hydrogel; PLGA; PLGA-PEG-PLGA; MESENCHYMAL STEM-CELLS; ENDOTHELIAL-CELLS; SMALL MOLECULES; DRUG-DELIVERY; ANGIOGENESIS; COCULTURE; REGENERATION; BIOMATERIALS; Materials Science